Development and Validation of a PBL-ESD-Based E-Student Worksheet for Chemical Equilibrium in Solutions - Putri, Tiara Swastika; Rohaeti, Eli; Yanti, Widya Ikhma (Universitas Sebelas Maret, 2025)
The need to improve critical thinking and scientific argumentation skills in chemistry highlights the importance of integrating Education for Sustainable Development (ESD) and Problem-Based Learning (PBL) into teaching materials. In the context of chemistry, ESD encourages students to relate chemical concepts to real-life environmental, social, and economic issues, while PBL encourages inquiry through real-world problem scenarios. This study aims to develop a digital student worksheet (E-LKM) that innovatively combines the ESD approach and the PBL learning model for the topic of chemical equilibrium in solution. Unlike conventional worksheets, this E-LKM presents sustainability-based dilemmas—such as pollution from industrial waste and its effects on equilibrium systems—designed to trigger discussion, collaboration, and higher-order thinking. This study used the Research and Development (R&D) method, using the Thiagarajan 4D model, involving 40 students and 5 chemistry education lecturers from Riau Province as samples. Data analysis included validation by experts and user feedback on the practicality and readability of the results. E-LKM obtained a validation score of 115 (very good), a practicality score of 71, and a readability score of 60.767—both of which were classified as very good. These results indicate that E-LKM is a valid and practical tool for supporting chemistry learning, with a focus on sustainability, critical thinking, and scientific argumentation